PENGGUNAAN MODEL DEMONSTRASI DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SD - Anggun Arini (EDUCATIONAL JOURNAL : General and Specific Research, 2026)
This study discusses the use of the demonstration learning model in science learning to improve the activity and learning outcomes of elementary school students. Science learning in elementary school often involves abstract concepts that are difficult for students to understand without concrete learning experiences. The demonstration model allows teachers to present scientific processes directly in the classroom so that students can observe real events and better understand the concepts being taught. This study uses a literature review method based on relevant educational books to explore the concept, implementation, advantages, limitations, and impact of the demonstration model. The findings show that the demonstration model can increase student learning activity by encouraging observation, questioning, and discussion during the learning process. In addition, learning outcomes improve because students gain direct experience that helps them understand and retain scientific concepts more effectively. Although this model has limitations such as dependence on teaching aids and time allocation, it remains an effective approach when properly designed and implemented by teachers.